Effect of Concentration and Interval of Giving Goat Urine Liquid Organic Fertilizer on Growth and Yield of Kailan (Brassica oleraceae L.) - Reyke Febrianti Rohmandita; A Miftakhurrohmat (Nabatia, 2023)
The effect of the concentration and interval of giving goat urine liquid organic fertilizer on the growth and yield of kailan. This study aims to determine the interaction between the concentration and interval of giving goat urine liquid organic fertilizer on the growth and yield of kailan. This research was conducted at Ds. Jatikalang Krian started in February – April 2023. The study used a factorial Randomized Block Design (RBD) consisting of 2 factors with 3 replications. The first factor is the POC concentration which consists of 4 levels, namely concentration of 60 ml/L, concentration of 90 ml/L, concentration of 120 ml/L, concentration of 150 ml/L. The second factor is the administration interval which consists of 3 levels, including 3 days, 5 days, 7 days. The research results show that the concentration of goat urine liquid organic fertilizer has an effect on the observation of the number of leaves, leaf area, wet weight and dry weight. While the time interval treatment only affects the plant height parameter. The combination of goat urine liquid organic fertilizer treatment with the time interval of application showed a significant interaction on the observation of kailan leaf area. The best concentration of goat urine liquid organic fertilizer is giving 120 ml with an interval of application every 5 days.